Peran Audit Internal dan Pengendalian Internal dalam Pencegahan Fraud di Era Digital : Systematic Literature Review - Amira Nabila; Trinandari Prasetya Nugrahanti (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
In the digital era, organizations face increasingly sophisticated fraud risks that threaten financial stability and stakeholder trust. The rapid adoption of digital technologies has amplified both the opportunities and complexity of fraudulent activities, necessitating stronger internal audit and internal control mechanisms. This study aims to analyze the role of internal audit and internal control in preventing fraud through a Systematic Literature Review (SLR) of 20 accredited articles published between 2021 and 2025. The research method involved systematically identifying, screening, and reviewing articles from reputable academic databases such as Scopus, Google Scholar, and national accredited journals. Articles were selected based on criteria including relevance to audit, internal control, fraud prevention, full-text availability, and publication in peer-reviewed journals. Data analysis was conducted using thematic analysis, categorizing findings according to key aspects of internal audit, internal control, and digital oversight. The synthesis reveals that internal audit contributes significantly to fraud prevention through risk assessment, control evaluation, and the application of digital technologies such as data analytics. Effective internal control systems, including control environment, supervision, risk assessment, and continuous monitoring, reduce fraud opportunities. Integration of internal audit, internal control, governance, and technology enhances overall fraud prevention effectiveness. The findings highlight the need for synergy between technological oversight and robust governance structures, providing guidance for future research and strategic fraud prevention frameworks.